(x-4)-4=-4x(4-3x)

Simple and best practice solution for (x-4)-4=-4x(4-3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-4)-4=-4x(4-3x) equation:


Simplifying
(x + -4) + -4 = -4x(4 + -3x)

Reorder the terms:
(-4 + x) + -4 = -4x(4 + -3x)

Remove parenthesis around (-4 + x)
-4 + x + -4 = -4x(4 + -3x)

Reorder the terms:
-4 + -4 + x = -4x(4 + -3x)

Combine like terms: -4 + -4 = -8
-8 + x = -4x(4 + -3x)
-8 + x = (4 * -4x + -3x * -4x)
-8 + x = (-16x + 12x2)

Solving
-8 + x = -16x + 12x2

Solving for variable 'x'.

Combine like terms: x + 16x = 17x
-8 + 17x + -12x2 = -16x + 12x2 + 16x + -12x2

Reorder the terms:
-8 + 17x + -12x2 = -16x + 16x + 12x2 + -12x2

Combine like terms: -16x + 16x = 0
-8 + 17x + -12x2 = 0 + 12x2 + -12x2
-8 + 17x + -12x2 = 12x2 + -12x2

Combine like terms: 12x2 + -12x2 = 0
-8 + 17x + -12x2 = 0

Begin completing the square.  Divide all terms by
-12 the coefficient of the squared term: 

Divide each side by '-12'.
0.6666666667 + -1.416666667x + x2 = 0

Move the constant term to the right:

Add '-0.6666666667' to each side of the equation.
0.6666666667 + -1.416666667x + -0.6666666667 + x2 = 0 + -0.6666666667

Reorder the terms:
0.6666666667 + -0.6666666667 + -1.416666667x + x2 = 0 + -0.6666666667

Combine like terms: 0.6666666667 + -0.6666666667 = 0.0000000000
0.0000000000 + -1.416666667x + x2 = 0 + -0.6666666667
-1.416666667x + x2 = 0 + -0.6666666667

Combine like terms: 0 + -0.6666666667 = -0.6666666667
-1.416666667x + x2 = -0.6666666667

The x term is -1.416666667x.  Take half its coefficient (-0.7083333335).
Square it (0.5017361113) and add it to both sides.

Add '0.5017361113' to each side of the equation.
-1.416666667x + 0.5017361113 + x2 = -0.6666666667 + 0.5017361113

Reorder the terms:
0.5017361113 + -1.416666667x + x2 = -0.6666666667 + 0.5017361113

Combine like terms: -0.6666666667 + 0.5017361113 = -0.1649305554
0.5017361113 + -1.416666667x + x2 = -0.1649305554

Factor a perfect square on the left side:
(x + -0.7083333335)(x + -0.7083333335) = -0.1649305554

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| 85=10-2.5c | | 2z-12=20 | | .142(2x+2)=1 | | 29(x+5)=3x+21 | | 85=2.5c | | -3p=-63 | | 242+155= | | 39-4x=28-8x+3 | | 48t=48t^2 | | -8+3r=-6+4(r-1) | | 9m-16=65 | | 5a=-50 | | 10k^2=4 | | 8y=-56 | | 13+7x=1+9x+21 | | 4(-4p)=64 | | 2-3x=7x-98 | | 4t=4t^2 | | 2a*4=20 | | 0=-2(y+3) | | 4x+2x+3=3x+x+7 | | 3x^2+33x+84= | | 5+(2x-3)=x-(3x+10) | | 26+x=(-4) | | 2v-2=-6 | | 4x-3=-29 | | 3.5=4-3x | | x^4-6x^2-7x-6=0 | | s+9=4 | | 5x-5=x+15 | | 5=3b | | 9x-18=3x |

Equations solver categories